Academic Goal Profiles and Learning Strategies in Adolescence - Martínez-Monteagudo, María Carmen; Delgado, Beatriz; Sanmartín, Ricardo; Inglés, Candido J.; García-Fernández, José Manuel (Frontiers in Psychology, 2018)
The objective of this study was to verify whether or not a combination of academic goals may be established in different profiles of high school students. Subsequently, the study examined if statistically significant differences exist between the profiles obtained with respect to learning strategies used by the students. The Achievement Goal Tendencies Questionnaire (AGTQ) and the Learning and Studies Skills Inventory-High School Version (LASSI-HS) were administered to a sample of 2,069 high school students aged 12 to 16 (M = 14.11; SD = 1.35) and which was formed by 1,073 girls and 996 boys. Four academic goal profiles were identified using latent class analysis: a group of students with a high academic goal profile (668 students), a group of students with a low academic goal profile (502 students), a group of students with a predominance of learning goals and achievement goals (489 students) and a final group of students with a predominance of social reinforcement goals and achievement goals (410 students). The results revealed statistically significant differences between the profiles obtained with respect to learning strategies because students from the combined Learning Goals and Achievement Goals (LGAG) and High Academic Goals (HAG) profiles used more learning strategies that those in the Low Academic Goals (LAG) and Achievement Goals and Social Reinforcement (AGSR)groups. However, the relationship between these motivational profiles and the obtainment of a higher academic performance has not been proven and it should be the subject of study in future research. Consequently, this study can be used to help in the development of strategies and intervention programs to promote the use of multiple academic goals in high school students.